The First Witnesses. Martha, Longinus and Veronica in the Slavic Manuscript Tradition (Initial Observations) - Skowronek, Małgorzata; Majer, Marek (Studia Ceranea, 2011)
The epithet ‘first witnesses’, conferred on the three saints in the title, is but a conventional designation; it seems fitting as common for the figures of saints, who gave proof of their devotion to Christ. Otherwise, although they make no simultaneous appearance in any of the canonical texts, there are – interestingly – far more interconnections between the three characters in pseudo-canonical and legendary literature than could be surmised from the lack thereof in the Bible. The aim of the paper is to present a literary picture of three New Testament heroes, as commemorated in different literary texts representing diverse cultural registers, even from the Ancient Christian Times until the close of the Middle Ages. Among them there are short and extended lives and passions of saints, liturgical poetry, as well as specific, more popular texts, such as ‘tales’ and legends. The material under discussion largely includes texts that form a part of the Slavic Orthodox tradition, depicting them on the background of fairly wellknown works belonging to the Western Christian tradition. It turns out that the legends are inspired by the canonical text on the one hand, while on the other hand they themselves infiltrate official texts – they become officially sanctioned as soon as their popularity is taken over and adopted by liturgical practice. It should be borne in mind that those legends – part of which is known both in the Eastern and in the Western Christianity – confirm one further crucial characteristic of texts constituting the canonical and pseudo-canonical tradition: the commonness of themes and motifs which can without exaggeration be called ‘wandering’. They determine the fact that there is hardly any originality in the formation of the characters of patron saints; moreover, on the level of creating the notion of sainthood and its reception, there seem to be far more common points than differences between both of the Early Christian traditions – the East and the West. The paper is an attempt to point out how the Christian tradition exemplifies various manifestations of holiness, what means it has for annotating, elucidating and embellishing the Biblical hypertext, and how it adapts pseudo-canonical legends for the purposes of liturgical use.